Structural changes in milk from different species during gastric digestion in piglets - Roy D; Moughan PJ; Ye A; Hodgkinson SM; Stroebinger N; Li S; Dave AC; Montoya CA; Singh H (Elsevier Inc and Fass Inc on behalf of the American Dairy Science Association, 2022)
This study investigated the structural and physicochemical changes that occur in milk, a naturally designed complex structured emulsion, during gastric digestion using the bottle-fed piglet as an animal model. The gastric digestions of cow, goat, and sheep milk were compared in male piglets euthanized at different postfeeding times to collect the stomach chyme. The cow and noncow milks separated into curd (aggregated caseins) and liquid (mostly soluble whey) phases in the piglet's stomach. For milk from all the species, the curd remained longer in the stomach because of its slow disintegration, whereas the liquid phase emptied readily. The majority of the fat globules were found to be entrapped within the protein network of the curd. The rate of release of fat globules was strongly dependent on the breakdown of the surrounding protein network of the curd. The consistency of the gastric curds changed as digestion progressed, with goat and sheep milk curds having relatively softer curd consistency and less fused protein networks, especially toward the end of digestion. This might have led to the lower protein and fat retention in the goat and sheep milk curds and relatively faster gastric emptying of these nutrients from goat and sheep milk in comparison to cow milk. This in vivo study provided new and enhanced understanding of the mechanisms of the gastric digestion of milk from different species. It may have implications for developing bioinspired structures for the controlled digestion and delivery of nutrients.
Keywords: gastric digestion and emptying; in vivo piglet; milk; protein coagulation; structure; Animals; Cattle; Digestion; Euthanasia, Animal; Female; Goats; Male; Milk; Sheep; Stomach; Swine